Features of phenotyping patients with heart failure with preserved ejection fraction - E. K. Serezhina; A. G. Obrezan (Российский кардиологический журнал)
The current classification of heart failure (HF) is based on the myocardium systolic function. However, due to the polyetiological nature of the HF with preserved ejection fraction (HFpEF) and its increasing prevalence and clinical significance, a more advanced approach to the clinical assessment of patients is needed to determine the management tactics focused on the patient's phenotype. At the same time, a single algorithm for phenotyping patients with HF has not been formulated yet. There is also no terminological unity in approaches. A review of 47 original articles published in the period from 2015 to 2022 in English on Elsevier, Pubmed, Web of Science databases with a following keywords "HFpEF", "phenotype", "clusters", "phenotypic spectrum", "diastolic dysfunction" makes it possible to identify several different approaches to phenotyping HFpEF, which are based on the etiology, pathophysiological mechanisms or clinical manifestations. Differences in the algorithms used for classification lead to the formation of groups of patients with different characteristics. Today it becomes obvious that in order to develop an optimal phenotyping approach and patient-oriented management of HFpEF, a combined analysis of a large number of anamnestic, clinical and paraclinical data is necessary. To solve such a problem, unified clustering system for HFpEF types should be created, which will be basis for phenotyping patients proposed by the authors.